Applied TEM Approach for Micro/Nanostructural Characterization of Carbon Nanotube Reinforced Cementitious Composites - Aich, Nirupam; Zohhadi, Nima; Khan, Iftheker A.; Matta, Fabio; Ziehl, Paul; Saleh, Navid B. (Journal of Research Updates in Polymer Science, 2012)
A novel colloidal technique for transmission electron microscopy (TEM) of graphitic nano-reinforced cementitious (GNRC) composites was developed. Single-walled and multiwalled nanotubes (SWNTs and MWNTs) were functionalized using an acid etching technique to obtain stable aqueous suspensions that were incorporated in the mix design of a cement paste. Effective functionalization was demonstrated by Raman spectroscopic measurements and time resolved dynamic light scattering measurements. The functionalized nano-reinforcement and binding characteristics were observed at the nanoscale for the first time using high resolution TEM imaging. Functionalized CNTs were found to be well distributed and preferentially associated with the cementitious matrix. This newly developed colloidal technique for TEM imaging of GNRC composites is a viable approach to characterize the interfacial compatibility between graphitic nano-reinforcement and cementitious matrices.